Ultrasonography and Doppler ultrasonography findings of children with iron deficiency anemia - Koç, Mustafa; Girgin, Feyza; Serhatlioğlu, Selami (My University, 2018)
Aim: Iron deficiency anemia (IDA) is an important health problem in children in the worldwide. It affects both growth and mental motor development. Iron decrease then irons deficiency (ID) occurs during the developing of IDA. In the literature, there is no information about ultrasonography (US) and Doppler US findings in the development of IDA. The aim of this study is to search the US and DopplerUS findings of liver, spleen and main vascular structures of children with the iron decrease, ID, and IDA.Material and Methods: This study including 160 patients who have the iron decrease (n=43), ID (n=52), and IDA (n=65) in laboratory findings. The control group was 50 children. The liver and spleen sizes with parenchymal echogenicity, CCA Vmax -Vmin, ICA Vmax -Vmin, their pulsatility (PI) and resistive index (RI) were measured.Results: 23 patients (35%) were diagnosed with hepatomegaly and 8 patients (12%) were diagnosed with splenomegaly having IDA. There was a statistically significant difference between the groups in terms of CCA Vmax -Vmin, ICA Vmax -Vmin, and also RI - PI index of CCA with ICA (p<0.05).Conclusion: Hepatomegaly and splenomegaly can be seen in IDA. Increasing of anemia cause changes in the vascular flow velocities, and also increase the blood volume of the brain. If anemia is detected at an early stage and treatment is regulated, cognitive disturbances will not occur in children. In the diagnosis, an US and a Doppler US examination are useful.
Keywords: Genel ve Dahili Tıp; Patoloji; Hematoloji; Tıbbi Laboratuar Teknolojisi